Managing diagnostic problem of syphilis manifested as chronic colitis and enteropathic arthritis in a 29 yo male: a case report - Auliya, Kamila; Nugroho, Cahyo Wibisono; Mumtaza, Hilya Itsnain (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Syphilis is a chronic sexually transmitted infection caused by Gram-negative bacterium, Treponema pallidum, known for its ability to mimic other diseases, leading to misdiagnosis and delayed treatment. We present a case of a 29 yo male with recurrent acute diarrhea, accompanied by fever, nausea, vomiting, prolonged mouth ulcers, and weight loss for the last three months. He was hospitalized multiple times due to the same recurrent problems. He was initially suspected for immunodeficiency diseases and was screened for HIV and hepatitis B, but both results came out negative. The patient was then suspected with malignancy of the gastrointestinal tract and underwent several examinations including; hematology workup, abdominal X-ray, gastroduodenoscopy, colonoscopy and biopsy. However, the result of all abdominal X-ray, biopsy and colonoscopy ruled out malignancy. The examinations discovered intraluminal ileocecal mass that is consist of lymphocytic cells, therefore the patient was diagnosed with chronic colitis and ileitis. The patient went to the clinic as scheduled with a new chief complain of other symptoms; painful spine and hip join movement, which added to his new diagnose of enterophatic arthritis and he was hospitalized for further diagnosis. During hospitalization, the patient was screened for another venereal disease i.e. syphilis, due to the everchanging symptomatology. He was being screened with VDRL, and later TPHA test. This case encompasses the complexity and challenges of diagnostic workup in non-suggestive findings of the disease syphilis as the Great Imitator.